Optimizing MSME income through the golden door: study of sharia financial literacy - Sukma Irdiana (Jurnal Mantik, 2023)
One of the reasons for the low performance of MSMEs in Indonesia is limited access to funds, which is largely caused by a lack of understanding and knowledge of MSMEs regarding financial institutions. Currently, the Islamic finance sector has experienced rapid growth, with various financial institutions providing financial products and services based on Islamic principles. This research aims to assess the level of sharia financial literacy and identify factors that influence the level of sharia financial literacy and their impact on the development of MSME businesses in the region. The research method used was a descriptive survey and an explanatory survey, with 33 MSMEs as respondents. Descriptive analysis is used to evaluate research data, and simple regression tests are used to identify relationships between the variables studied. The research results show that only the variables "Length of Business" and "Number of Employees" have a significant influence on the level of financial knowledge. Meanwhile, demographic variables have no effect on the financial behavior and attitudes of street vendors. Only financial behavior has an influence on the development of street vendors' businesses, while financial knowledge and financial attitudes do not have a significant influence on the development of the business.